2021
DOI: 10.3390/en14248288
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Concentration of Propionic Acid in an Aqueous Solution by POD-GP Model and Spectroscopy

Abstract: Biorefining and biorefineries are the future of industry and energy. It is still a long way to complete its implementation, but small biorefineries focused mainly on the production of fuels and energy are more and more frequent in rural areas and large areas located near big cities in which, in addition to fuels and energy, various organic substances of high market value are also produced. In order to optimize biogas production and to control methane fermentation processes, fast and accurate identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The Gaussian process is fully defined by the mean function µ such that is the mean of and the covariance/kernel function such that is the covariance between the value of the function at , and the value of the function at , . Without going into details, because there are many textbooks and books on this subject, in recent scientific papers, one can also find details of their implementation [ 61 , 64 ]; the most important thing from the point of view of regression accuracy is the proper selection of kernel functions and proper training of hyperparameters.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gaussian process is fully defined by the mean function µ such that is the mean of and the covariance/kernel function such that is the covariance between the value of the function at , and the value of the function at , . Without going into details, because there are many textbooks and books on this subject, in recent scientific papers, one can also find details of their implementation [ 61 , 64 ]; the most important thing from the point of view of regression accuracy is the proper selection of kernel functions and proper training of hyperparameters.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible to find the unknown parameters using any optimization procedure. In the literature, one can find methods, in which a searching for the most probable set is performed by maximizing the log likelihood function [ 61 , 64 ] using any gradient-based optimization algorithms, e.g., a first-order batch Levenberg–Marquardt algorithm already presented in the previous section.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example could be the paper of Staszak et al [13], in which it was shown that the precast concrete slabs reinforced with spatial linear trusses may be efficiently homogenized to one effective layer of a representative shell element. On the other hand, the computational time (ii) can be reduced by using soft computing methods such as the artificial neural network (ANN) algorithms [14][15][16][17][18] or metamodeling [19,20]. This usually requires a significant computational effort, which is incurred before the solution of the target computational problem is needed, but it allows one to obtain a solution with an acceptably small error in a fraction of a second when the actual problem occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The present work is an extension of the work presented by Zaborowicz [ 29 ]. New elements that are additionally included here are: (a) automatic sensitivity analysis of all 21 indices to see which of them carry more information; (b) the use of data compression techniques based on the Proper Orthogonal Decomposition (POD) [ 30 , 31 , 32 , 33 ], which allows not only the reduction of the size of the input vector but also the denoising of the data, thereby reducing the risk of overfitting the model; (c) the use of Gaussian processes (GP) [ 34 , 35 ], which allows results and their uncertainty to be obtained. This model is trained once-for-all and can later be used as a ready-made tool for in situ identification of the dental age of new patients.…”
Section: Introductionmentioning
confidence: 99%